PERANCANGAN TAMAN WISATA EDUKASI DENGAN PENDEKATAN ARSITEKTUR EKOLOGI DI KOTA BENGKULU (Teknosia, 2023)
The city of Bengkulu has various tourist objects both natural, cultural and artificial tourism. One of the tourist objects that has the potential to be developed and does not get more attention from the government is artificial tourism. There are still very few man-made tourist objects in the city of Bengkulu and seen from the availability of attractions, amenities and tourism accessibility that are not good in several parks that are used as green open spaces. The function of the park is not only as an object of recreation but can be developed into a tour that can educate the public. The application of ecological architecture in the design of Educational Tourism Parks is an effort to create buildings that pay attention to environmental balance while at the same time providing awareness and knowledge to the public about protecting the environment. By applying the principles of ecological architecture to the treatment of waste in buildings, the layout of the building mass, the shape of the building, and the use of materials. So that the Educational Tourism Park with an ecological architectural approach can become a place of education for all people and can minimize the impact of environmental damage.